1997
DOI: 10.1074/jbc.272.29.18304
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-independent Dimerization of the Extracellular Domain of the Leptin Receptor and Determination of the Stoichiometry of Leptin Binding

Abstract: The leptin receptor is a class I transmembrane protein with either a short or a long cytoplasmic domain. Using chemical cross-linking we have analyzed the binding of leptin to its receptor. Cross-linking of radiolabeled leptin to different isoforms of the leptin receptor expressed on COS-1 cells reveals leptin receptor monomer, homodimer, and oligomer complexes. Cotransfection of the long and short form of the leptin receptor did not provide any evidence for the formation of heterodimer complexes. Soluble form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
3
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 31 publications
4
98
3
7
Order By: Relevance
“…4C, free leptin (fraction 90, 16-17 kDa) was efficiently separated from the bound form of leptin (fraction 58, 310 kDa). The size of the bound form of leptin is consistent with leptin binding to dimers of ObRe (19). Free leptin fraction represented Ϸ65% of total leptin in the Ob͞ϩ mouse serum and only 5.4% in ApoE-ObRe;Ob͞ϩ mouse serum.…”
Section: Comparison Of Antiosteogenic and Anorexigenic Functions Of Lmentioning
confidence: 66%
“…4C, free leptin (fraction 90, 16-17 kDa) was efficiently separated from the bound form of leptin (fraction 58, 310 kDa). The size of the bound form of leptin is consistent with leptin binding to dimers of ObRe (19). Free leptin fraction represented Ϸ65% of total leptin in the Ob͞ϩ mouse serum and only 5.4% in ApoE-ObRe;Ob͞ϩ mouse serum.…”
Section: Comparison Of Antiosteogenic and Anorexigenic Functions Of Lmentioning
confidence: 66%
“…Cytokine receptors contain no intrinsic enzymatic activity but transmit signals via noncovalently associated Jak family tyrosine kinases (47). Ligand binding to the leptin receptor, which exists on the membrane as a preformed homodimer (16,25,48), probably initiates signaling by inducing a conformational change in LRb that brings the constitutively LRb-associated intracellular Jak2 molecules into close apposition, enabling their transphosphorylation. Tyrosine phosphorylation of Jak2 on Tyr 1007 and Tyr 1008 of a regulatory loop within the Jak2 tyrosine kinase domain leads to kinase activation (24,49), resulting in further tyrosine phosphorylation of Jak2 and of two residues in the intracellular domain of LRb, Tyr 985 and Tyr 1138 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…receptors for growth hormone, erythropoietin, and prolactin) form homodimers when activated by ligand, while others form hetero-oligomers (12)(13)(14). Recent studies have shown that leptin receptors form homodimers, both in the presence and absence of ligand (15,16). Each leptin receptor binds one molecule of leptin, resulting in a tetrameric complex composed of two receptors and two leptin molecules.…”
mentioning
confidence: 99%
“…Each leptin receptor binds one molecule of leptin, resulting in a tetrameric complex composed of two receptors and two leptin molecules. However, activation of the receptor is thought to result from a ligand induced conformational change rather than dimerization of the receptor (15,17). All the leptin receptor isoforms contain a "box 1" Janus kinase binding site in the cytoplasmic domain.…”
mentioning
confidence: 99%